The impact of permanent early-onset unilateral hearing impairment in children – A systematic review. (May 2019) - Huttunen, Kerttu; Erixon, Elsa; Löfkvist, Ulrika; Mäki-Torkko, Elina
Abstract: Background: Decision-making on treatment and (re)habilitation needs to be based on clinical expertise and scientific evidence. Research evidence for the impact of permanent unilateral hearing impairment (UHI) on children's development has been mixed and, in some of the reports, based on fairly small, heterogeneous samples. Additionally, treatment provided has been highly variable, ranging from no action taken or watchful waiting up to single-sided cochlear implantation. Published information about the effects of treatment has also been heterogeneous. Moreover, earlier reviews and meta-analyses published on the impact of UHI on children's development have generally focused on select areas of development. Objectives: This systematic review aimed to summarize the impact of children's congenital or early onset unilateral hearing impairment on listening and auditory skills, communication, speech and language development, cognitive development, educational achievements, psycho-social development, and quality of life. Methods: Literature searches were performed to identify reports published from inception to February 16th, 2018 with the main electronic bibliographic databases in medicine, psychology, education, and speech and hearing sciences as the data sources. PubMed, CINALH, ERIC, LLBA, PsychINFO, and ISI Web of Science were searched for unilateral hearing impairment with its synonyms and consequences of congenital or early onset unilateral hearing impairment. Eligible were articles written in English, German, or Swedish on permanent unilateral hearing impairments that are congenital or with onset before three years of age. Hearing impairment had to be of at least a moderate degree with PTA ≥40 dB averaged over frequencies 0.5 to 2 or 0.5–4 kHz, hearing in the contralateral ear had to have PTA0.5–2 kHz or PTA0.5–4 kHz ≤ 20 dB, and consequences of unilateral hearing impairment needed to be reported in an unanimously defined population in at least one of the areas the review focused on. Four researchers independently screened 1618 abstracts and 566 full-text articles for evaluation of study eligibility. Eligible full-text articles were then reviewed to summarize the results and assess the quality of evidence. Additionally, data from 13 eligible case and multi-case studies, each having less than 10 participants, were extracted to summarize their results. Quality assessment of evidence was made adapting the Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) process, and reporting of the results adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards. Results: Three articles with the quality of evidence graded as very-low to low, fulfilled the eligibility criteria set. Due to the heterogeneity of the articles, only a descriptive summary could be generated from the results. Unilateral hearing impairment was reported to have a negative impact on preverbal vocalization of infants and on sound localization and speech perception both in quiet and in noise. Conclusions: No high-quality studies of consequences of early-onset UHI in children were found. Inconsistency in assessing and reporting outcomes, the relatively small number of participants, low directness of evidence, and the potential risk of confounding factors in the reviewed studies prevented any definite conclusions. Further well-designed prospective research using larger samples is warranted on this topic.